The Influence of Service Quality and Facilities on Customer Satisfaction of PT Indonesia Penuh Rezeki (Case Study of Pelindo Petikemas Belawan Employee Gathering Event) - Ramadhan, Dwiyan; Purnami, Suri (Journal of Economics and Social Sciences (JESS), 2025)
The increase in the number of employees taking part in Pelindo Petikemas Belawan employee gathering events is a phenomenon in this research. To provide customer satisfaction there are several factors namely service quality and facilities. This research aims to find out whether the quality of service and facilities influences customer satisfaction in the case study of the Pelindo Petikemas Belawan Employee Gathering event. Research method The population of this study was 1,400 people and the sample used was 93 respondents (Slovin). Data collection was carried out through questionnaires distributed in the form of Google forms via social media and through literature studies in the form of primary and secondary data. This research uses quantitative research methods which include validity testing, reliability testing, classical assumption testing, hypothesis testing. The research results show that partially the quality of services and facilities has a significant positive influence on customer satisfaction and simultaneously the quality of services and facilities has a significant positive influence on customer satisfaction. Facilities have a more dominant influence than service quality and based on the results of the coefficient of determination test, the variables of service quality and facilities influence customer satisfaction by 63.3% and the remaining 36.7% is influenced by other variables not examined in this research.